A review on the factors contributing to non-communicable disease (NCD) among low-wage workers - Abdul Rahman, Haliza; Abu Bakar, Azrin Shah; Kadir Shahar, Hayati; Mohd Nazan, Ahmad Iqmer Nashriq (Universiti Putra Malaysia, 2021)
Low-wage workers significantly contribute to the nation’s continuous economic growth and prosperity. However, they were more vulnerable to non-communicable disease (NCD) than other workers, where, is mostly research focuses on Western countries-impose on large shares of the population in Asian countries has received far less attention. In view of this concern, this study attempts to identify the factors that may contribute to NCD among low-wage workers in Asia. This review applied the literature search method as the main methodology. Existing literatures in English languages from year 2011 to 2020 were identified. The database search was inclusive of PubMed and Google Scholar. A total of 16 studies that met the inclusion criteria were selected for this review. Findings from this review highlighted factors contributing to NCD, which were further divided into five categories, i.e., socio-demographic factors, behavioural factors, work-related factors, biological factors and psychosocial factors. These factors contribute to the NCD such as overweight, hypertension, diabetes, cardiovascular diseases and musculoskeletal disorders among low-wage workers. Identifying these factors contribute to a better understanding of NCD and risk factors among this population group.